Telegram from William Randolph Hearst to Julia Morgan, November 9, 1927 - William Randolph Hearst::::::author::: (1927)
Handwritten notes on back reading "1926 Total per month for all animal provisions etc - including work horses = $608.50 (This includes food for work horses but not care of stable, as teamsters handle that)" may or may not be by/for Julia Morgan.